2018
DOI: 10.1111/jon.12504
|View full text |Cite
|
Sign up to set email alerts
|

Early Blood‐Brain Barrier Disruption after Mechanical Thrombectomy in Acute Ischemic Stroke

Abstract: Moderate BBB disruption is common after mechanical thrombectomy in a quarter of patients with acute ischemic stroke and increases the risk of intracranial hemorrhage and poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…In any of the cases, HT occurs when cerebral blood flow is restored to damaged blood vessels weakened by ischemic stroke (47,66). In fact, the disruption and leakiness of the BBB on pretreatment imaging is correlated with the severity of HT (123). Furthermore, a higher BBBP is associated with not only the severity of but also the likelihood to develop HT (64,124,125).…”
Section: Hemorrhagic Transformation: the Role Of Bbb Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In any of the cases, HT occurs when cerebral blood flow is restored to damaged blood vessels weakened by ischemic stroke (47,66). In fact, the disruption and leakiness of the BBB on pretreatment imaging is correlated with the severity of HT (123). Furthermore, a higher BBBP is associated with not only the severity of but also the likelihood to develop HT (64,124,125).…”
Section: Hemorrhagic Transformation: the Role Of Bbb Permeabilitymentioning
confidence: 99%
“…Dual-energy head CT is currently the gold standard to distinguish both conditions in control CT post-EVT (147,148). One study (123) found BBB disruption evaluated by non-contrast CT scan within 3 h of the procedure and defined as parenchymal hyperdensity on CT scan (including both blood and contrast medium), occurring in 61% of patients. Multiple thrombectomy passes have also been independently associated with a significant increase in BBB disruption as evaluated by hyperintense acute reperfusion marker (HARM) which is a hyperintensity on T2-weighted fluid-attenuated inversion recovery (FLAIR) MRI following an injection of gadolinium-based contrast agent (149).…”
Section: Ht Motivated By Reperfusion Treatments: Thrombolysis and Endmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, hyperdense lesions apparent on postprocedural computed tomography (CT) after EVT are common and may be secondary to contrast extravasation or intracerebral hemorrhage (ICH). 2,3 Contrast extravasation is believed to be caused by leakage from vessels into extracellular spaces due to increased permeability of the blood brain barrier (BBB), [4][5][6] which relates to increased risk of hemorrhagic transformation (HT) 2,7-9 and poor prognosis. 5,8,10 Therefore, identification of these high-density lesions on CT as contrast extravasation or ICH is critical and has significant clinical ramifications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mTBI can be associated with a rapid disruption of blood-brain barrier (BBB) integrity followed by eventual development of brain damage [e.g., (7)(8)(9)]. BBB disruption after TBI is also a risk factor for secondary brain hemorrhage (10)(11)(12). It is therefore important to detect early BBB disruption to predict the development of persistent post-concussion disability.…”
Section: Introductionmentioning
confidence: 99%